THE ROLE OF RELIGIOUS LITERACY IN COUNTERACTING NEW ISLAMIST MOVEMENTS IN KAZAKHSTAN - KNYSH, Alexander; BAITENOVA, Nagima; NURSHANOV, Azamat; PARDABEKOV, Dias (CENTRAL ASIA AND THE CAUCASUS, 2019)
The paper focuses on the critical role of educational institutions in disseminating a sophisticated and historically grounded understanding of religion among young people of post-Soviet Kazakhstan. In the context of a plurality of opinions, worldviews, and cultural and religious products available in today's global marketplace, one can hardly expect any restrictive measures and bans imposed by the government to prevent Kazakh youth from getting exposed to non-systemic and alternative religious movements, including those with militant agendas. The rapid development of modern communication technologies renders all kinds of information readily available to the young generation of Kazakhs through virtual forums, blogs, and chatrooms. Invisible and anonymous recruiters for various religious-political causes and religious cults exploit this fact to their advantage, using the legitimate grievances of young people that the state is unwilling or unable to address. The situation in Kazakhstan is further aggravated by the fact that the majority of the population, especially its youth, has a very vague knowledge of their own religion, not to mention the religions that are not part of their personal background or family tradition. Under these circumstances, the issue of religious education requires close attention from both researchers and policymakers. The authors see education as the key factor in immunizing young Kazakhs against religious extremism, close-mindedness, and religion- and ethnicity-based intolerance and hatred.